Factors affecting Earnings Quality - Alvin Alvin; Yulius Kurnia Susanto (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The research aims to obtain empirical evidence about factors that affect earnings quality, particularly, the influence of auditor size, audit tenure, audit specialization, firm size, audit committee, leverage, investment opportunity set (IOS), growth opportunity, managerial ownership, and institutional ownership on earnings quality. The population used in this research are all manufacturing companies that are listed in Indonesia Stock Exchange from 2014-2020 and use purposive sampling as the sampling method. Through this method, forty-five (45) manufacturing companies fit with the sampling criteria and chosen as the sample with a total of 135 data. This research uses multiple regression method to analyse the data. The results of multiple regressions show that auditor size, audit tenure, audit specialization, firm size, and leverage have an effect on earnings quality, while the other 5 variables, which are investment opportunity set (IOS), growth opportunity, managerial ownership, and institutional ownership has no effect on earnings quality. Audit specialization has positive effect on earnings quality as those auditors will have deeper understanding regarding the industry, enabling them to better ensure earnings is of high quality.